Children's understanding of human–nature interaction after a folk storytelling session - Yılmaz, Simge; Temiz, Zeynep; Karaarslan Semiz, Güliz (Applied Environmental Education & Communication, 2020)
The purpose of this study is to investigate how children express human–nature interactions after a folk storytelling session. In order to accomplish this task, a Turkish folk story was told to thirteen five-year-old Turkish preschool children. Subsequently, the children were asked to retell the story and semi-structured interviews related to the story were conducted with each of them. Findings revealed that folk stories like the Nasreddin Hodja story in this study could be a useful means for children to understand interconnections in nature and be respectful and feel empathy towards living things in nature. Teachers and educators should design more environmental storytelling activities for children.
Publisher: Routledge _eprint: https://doi.org/10.1080/1533015X.2018.1517062